2013
DOI: 10.7554/elife.01295
|View full text |Cite
|
Sign up to set email alerts
|

Massive palmitoylation-dependent endocytosis during reoxygenation of anoxic cardiac muscle

Abstract: In fibroblasts, large Ca transients activate massive endocytosis (MEND) that involves membrane protein palmitoylation subsequent to mitochondrial permeability transition pore (PTP) openings. Here, we characterize this pathway in cardiac muscle. Myocytes with increased expression of the acyl transferase, DHHC5, have decreased Na/K pump activity. In DHHC5-deficient myocytes, Na/K pump activity and surface area/volume ratios are increased, the palmitoylated regulatory protein, phospholemman (PLM), and the cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
89
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 55 publications
(78 reference statements)
4
89
0
Order By: Relevance
“…DHHC5 regulates Na pump density at the cell surface via MEND (8). Consistent with our previous investigation (9) we found no influence of PLM or its palmitoylation status on cell surface expression of the pump α-subunit (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…DHHC5 regulates Na pump density at the cell surface via MEND (8). Consistent with our previous investigation (9) we found no influence of PLM or its palmitoylation status on cell surface expression of the pump α-subunit (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…DHHCs 2 and 3 possess notably little disorder, which may account for their tractability in cell-free systems (20). In some isoforms the region of C-tail disorder is relatively large (for example, DHHCs 1,5,8,and 14). Our experimental data together with these disorder predictions are consistent with previous reports that regions outside the cysteinerich domain are responsible for substrate recruitment to DHHCs (27)(28)(29).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It has been reported that some cardiac proteins are palmitoylated, including Na pump regulatory subunit phospholemman and β1-adrenergic receptor (20)(21)(22). However, there is a lack of genetic evidence that protein palmitoylation plays a role in heart development and function.…”
mentioning
confidence: 98%